The identity of Tachina westermanni Wiedemann, 1819 (Diptera: Calliphoridae or Tachinidae) with a solution to a nomenclatural problem - Rognes, Knut; O’hara, James E.; Cerretti, Pierfilippo (Zootaxa, 2015)
Tachina westermanni Wiedemann, 1819 was based on four syntypes, two conspecific calliphorids and two conspecific tachinids. Two existing but contradictory lectotype fixations have resulted in confusion as to the correct application of the specific name westermanni Wiedemann. Evidence is presented showing that the lectotype fixation of Townsend in 1931 is valid and assigns westermanni Wiedemann to the Calliphoridae, with Pericallimyia westermanni as the valid binomen. The valid name for the tachinid taxon becomes Brachelia westermanni Robineau-Desvoidy, 1830 and a neotype is designated for it in the interests of nomenclatural stability.